A novel coumarin derivative as a sensitive probe for tracing intracellular pH changes1. Issue 21 (6th March 2015) - Liu, Mengqiang; Hu, Minshan; Jiang, Qian; Lu, Zhiyun; Huang, Yan; Tan, Yanfei; Jiang, Qing
<x xml:space="preserve">Abstract</x> A novel coumarin derivative was synthesized and its application in live cell imaging was demonstrated.